Italian Community Psychology in the COVID-19 Pandemic: Shared Feelings and Thoughts in the Storytelling of University Students - Di Napoli, Immacolata; Guidi, Elisa; Arcidiacono, Caterina; Esposito, Ciro; Marta, Elena; Novara, Cinzia; Procentese, Fortuna; Guazzini, Andrea; Agueli, Barbara; Gonzáles Leone, Florencia; Meringolo, Patrizia; Marzana, Daniela (Frontiers in Psychology, 2021)
This study investigated how young Italian people experienced the period of peak spread of COVID-19 in their country by probing their emotions, thoughts, events, and actions related to interpersonal and community bonds. This approach to the pandemic will highlight social dimensions that characterized contextual interactions from the specific perspective of Community Psychology. The aim was to investigate young people's experiences because they are the most fragile group due to their difficulty staying home and apart from their peers and because they are, at the same time, the most potentially dangerous people due to their urge to gather in groups. The research involved 568 university students, 475 females, and 93 males, with an average age of 21.82 years (SD = 4.836). The collected data were analyzed with the Grounded Theory Methodology, using the Atlas 8.0 software. From the textual data, representative codes were defined and grouped into 10 categories, which reflect the individuals' prosocial attitudes, behaviors, and values. These categories formed three macro-categories, called: “Collective Dimensions,” which includes Connectedness, Solidarity, Italian-ness, Social Problems, and Collective Mourning; “Prosocial Orientation,” which includes Trust and Hope; and “Collective Values,” which includes Values of Freedom, Respect of Social Rules, and Civic-Mindedness. All these macro-categories are indicative of the shared feelings experienced by Italians during the first time of the pandemic. Further practical implications of these results will be discussed, including a consideration of the risk of developing distress and improving well-being, as well as promoting preventive behaviors.